ULX spectra revisited: Are accreting, highly magnetized neutron stars the engines of ultraluminous X-ray sources? - Koliopanos, F.; Vasilopoulos, G.; Bachetti, M.; Godet, O.; Webb, N.; Barret, D. (2017)
In light of recent discoveries of pulsating ULXs and recently introduced models placing neutron stars as the central engines of ULXs, we revisit the spectra of seventeen ULXs, in search of indications that favor this hypothesis. To this end we examined the spectra from XMM-Newton observations of all seventeen sources in our sample. For six sources, these were complimented with spectra from public NuSTAR observations. We demonstrate that the notable ({>}6 keV) spectral curvature observed in most ULXs, is most likely due to thermal emission, with T{>} 1keV. More importantly, we find that a double thermal model (comprised of a 'cool' and 'hot' thermal component) - often associated with emission from neutron star X-ray binaries - describes all ULX spectra in our list. We propose that the dual thermal spectrum is the result of accretion onto highly magnetized NSs, as predicted in recent theoretical models (Mushtukov et al. 2017). We further argue that this finding offers an additional and compelling argument in favor of neutron stars as prime candidates for powering ULXs, as has been recently suggested (King & Lasota 2016; King et al. 2017). In my talk I will discuss the implications of our interpretation along with its merits and shortcomings.